2017
DOI: 10.1149/07711.1053ecst
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Upscaled Microbial Fuel Cells in Real Municipal Sewage Plants

Abstract: Microbial fuel cells (MFC) are a promising technology to enhance the power-efficiency of municipal sewage plants. Therefore, the possibilities of MFC implementation on municipal sewage treatment plants are analyzed in this contribution.A newly developed up-scaled cell design is described, each with an active area of 6,200 square centimeters respectively. The cell design integrates a double-sided graphite/polymer composite anode between two oxygen reducing cathodes, to enlarge the active surface area. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
6
0
1
Order By: Relevance
“…It can be observed that nowadays, about 60 % of the studies related to MFCs use synthetic substrates, mainly glucose and acetate. Synthetic wastewater is frequently employed in MFCs, but its operation with real municipal and industrial wastewaters has also been tested satisfactorily . About 40 % of the studies use natural substrates, the sources of which show great diversity: raw domestic wastewater (40 %), marine sediments (25 %), and sewage sludge (10 %).…”
Section: Scale‐up Of Mfcs: What Are the Technology Facts And Limitatimentioning
confidence: 99%
“…It can be observed that nowadays, about 60 % of the studies related to MFCs use synthetic substrates, mainly glucose and acetate. Synthetic wastewater is frequently employed in MFCs, but its operation with real municipal and industrial wastewaters has also been tested satisfactorily . About 40 % of the studies use natural substrates, the sources of which show great diversity: raw domestic wastewater (40 %), marine sediments (25 %), and sewage sludge (10 %).…”
Section: Scale‐up Of Mfcs: What Are the Technology Facts And Limitatimentioning
confidence: 99%
“…The upscaling to higher m 3 volumes has so far been solved by the modular setup of MFCs that work independently from one another. This approach has enabled pilot plants to treat working volumes from 686 up to 1000 L . A conversion from the pilot scale to the industrial scale with reactors based solely on electroactive microorganisms has not been performed until recently, since the power generation is not sufficient yet , .…”
Section: Introductionmentioning
confidence: 99%
“…Newer studies focus on more complex MnO2-based The net power generation of MFCs is rather low, especially due to the performance-limiting cathode [9][10][11][12]. To overcome this bottleneck, large electrode surfaces [13], improved cathode manufacturing methods, and especially scalable methods are needed [5]. In the laboratory, cathodes for MFCs are often prepared by brushing [9,[14][15][16][17][18], dipping [19], rolling [20], pressing [21], doctor blading [12], spin coating [22], or electro deposition [19,23].…”
Section: Introductionmentioning
confidence: 99%